Determinants of Stress Among Secondary School Teachers in Kubang Pasu District - Siti Hajar, Ahmad Jais (2010)
This study seeks to determine the factors and the dominant stress factors among secondary school teachers in the Kubang Pasu district, Kedah. Three secondary schools in Kubang Pasu district which were randomly selected. 121 teachers from the selected schools are participating in the study. A questionnaire was used to determine socio-demographic background, working information and stress factors. Results showed that most of the teachers experience moderate stress level (mean value at 3.319). In terms of these factors are found all the factors which are workload, student misbehavior, professional recognition, classroom resources and poor colleague relations had been given moderate pressure on the teachers involve. However, in this study workloads are the dominant factors leading to teacher stress. In general, the study reveals that the theory of teachers stress is capable in predicting the causes of the stress among secondary teachers in Kubang Pasu district.